Design and synthesis of boric acid-based deep eutectic solvents for green liquid superlubricity and bio-lubrication applications - Qiulong Gao; Jinxia Hu; Dong Pei; Zhangpeng Li; Jinqing Wang; Shengrong Yang (Next Materials, 2025)
Research on the chemical structures and physicochemical properties of deep eutectic solvents (DESs) is crucial to develop high-performance DES-based lubricating materials for solving tribological problem, including friction and wear. Herein, a series of boric acid-based DESs (B-DESs) were synthesized using choline chloride (hydrogen bond acceptor, HBA) and sorbitol/boric acid (hydrogen bond donors, HBDs) through a simple heating-stirring method. The experimental investigations and quantum chemistry calculation demonstrated that B-DESs exhibited optimized chemical structures, favorable rheological properties, low melting points (below −61.6 °C), high thermostability (with decomposition temperatures exceeding 282 °C), and biocompatibility. As lubricants, they showed exceptional tribological performance, achieving macroscale superlubricity with a friction coefficient of ∼0.0088 and excellent anti-wear properties on polyoxymethylene substrates even under high-load conditions. The exceptional lubrication performance was attributed to synergetic lubrication between the fluid nature of B-DESs and the self-lubrication property of the substrates, as well as the potential formation of lubricating films at the tribo-interface. This study introduces a novel and straightforward approach for synthesizing green and high-performance DES-based liquid superlubricity materials, and offering significant potential in bio-lubrication applications.